Body Mass Index and Warm Compress Are Associated with Severity of Dysmenorrhea in Jakarta Private High Schools - Sri Rezeki Handayani Sinurat; Regina Vidya Trias Novita (Universitas Muhammadiyah Surakarta, 2022)
Dysmenorrhea is pain during menstruation that can disturb teenager's daily activities, such as studying and social activities. Dysmenorrhea has a negative impact on the quality of life. Dysmenorrhea occurs in many women, especially at school age. The purpose of this study is to determine the relationship between characteristics and non-pharmacological pain management with the severity of dysmenorrhea among femalestudent at Yadika 2 Jakarta high school. This study used quantitative method, descriptive correlational design and cross sectional approach. The sample was 140 female students with a total sampling technique. This analysis was done by Chi Square found there is a colleration beteween characteristics menstrual cycle (pvalue=0.041), BMI (pvalue=0.001), and non-pharmacological pain management warm compress (pvalue=0.014) with the severity of dysmenorrhea. Adolescents are expected to be able to maintain a balanced nutritional diet to keep a normal BMI, and non-pharmacological treatment with warm compress can be an alternative to overcome dysmenorrhea